Terror What's Next.
This paper introduces a report that carefully examines how much of a role advanced technology has in the fight against terrorism. The report suggests that while only a few terrorist scenarios have obvious technical countermeasures, developed societies can count on superior technology in their effort to track, spy and fight terrorists, insurgents and militiamen
Keywords: Insurgents; Militiamen; Superior technology; Terrorist scenarios